2021
DOI: 10.1002/asia.202100635
|View full text |Cite
|
Sign up to set email alerts
|

Thermally‐Induced Intramolecular [4+2] Cycloaddition of Allylamino‐ or Allyloxy‐Tethered Alkylidenecyclopropanes

Abstract: A thermally‐induced intramolecular [4+2] cycloaddition reaction of allylamino‐ or allyloxy‐tethered alkylidenecyclopropanes has been reported in this paper, giving a new protocol for the rapid construction of polycyclic skeleton molecules in moderate to excellent yields with a broad substrate scope. On the basis of control experiments and DFT calculations, we disclosed that the reaction proceeded through a [4+2] cycloaddition and trace of water assisted 1,3‐H shift process to give the target product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…In this paper, we attempt to provide a thorough understanding of the reaction mechanism as well as the nature of product selectivity via a series of mechanistic studies, which is expected to enlighten the related rhodium-catalyzed reactions. In general, this direct 1,3-proton transfer is difficult due to the high energy barrier [ 24 , 25 ]; thus, we had to consider whether there are other factors to assist in the formation of product 3 . Previous reports [ 26 , 27 , 28 , 29 , 30 ] revealed that trace amounts of water in the reaction system could promote the reactions; therefore, we started to consider the influence of trace amounts of water in the reaction system on this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we attempt to provide a thorough understanding of the reaction mechanism as well as the nature of product selectivity via a series of mechanistic studies, which is expected to enlighten the related rhodium-catalyzed reactions. In general, this direct 1,3-proton transfer is difficult due to the high energy barrier [ 24 , 25 ]; thus, we had to consider whether there are other factors to assist in the formation of product 3 . Previous reports [ 26 , 27 , 28 , 29 , 30 ] revealed that trace amounts of water in the reaction system could promote the reactions; therefore, we started to consider the influence of trace amounts of water in the reaction system on this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that in these cases, additional water was necessary to be added into the reaction system as a proton source to accelerate the proton transfer process efficiently. 17 Unfortunately, some limitations of this newly developed HAT and proton transfer reaction were observed for several substrates. For example, when non-cyclic tetrasubstituted olefin 1ai was employed as a substrate, no reaction occurred under the standard conditions, probably due to the steric hindrance leading to the non-occurrence of the 1,5-HAT process.…”
Section: Introductionmentioning
confidence: 99%
“…9 d However, when the solvent was replaced with a mixture of MeCN and H 2 O (6 : 1), the target product 1ae was obtained in 78% yield as a sole product under otherwise identical conditions (Scheme 2e) (see Table 2 as well). This result suggests that the ambient H 2 O in the reaction system is likely to accelerate the proton transfer process, 17 and as for substrates bearing sterically large groups, the reaction efficiency can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…10 Thus, MCPs have been usually used as a good carrier of the three-membered ring to use their connected exocyclic double bonds undergoing the cyclization reaction with dienes, olefins and so on for the construction of polycyclic skeletons. 11–13 Herein, we report a thermally-induced intramolecular [2 + 2] cycloaddition of allene-MCPs for the rapid construction of two separable nitrogen-containing spiro[bicyclo[3.2.0]heptane-6,1′-cyclopropane] and spiroheptane-2,1′-cyclopropane polycyclic heterocycles upon heating at <70 °C in one step (a relatively mild condition) (Scheme 1, this work).…”
mentioning
confidence: 99%